Synergy Of Top Management Team Characteristics, Corporate Governance And Social Responsibility: How Performance Of Large Manufacturing Firms Changed - Mugwang’a, Julius Ogola; Awino, Zachary Bolo; Ogutu, Martin; Maalu, Jackson (Archives of Business Research, 2018)
The study examines the joint effect of top management team characteristics, corporate governance and corporate social responsibility on organizational performance of large manufacturing firms. The study is guided by the upper echelons, agency, stakeholder and organizational performance theories respectively. A descriptive cross-sectional survey design was adopted. The population was all seventy two large manufacturing firms in Kenya. Primary data was collected using structured questionnaire from Chief Executive Officers. This was analysed through descriptive and multiple regression analysis. Results obtained show that the synergy of top management team characteristics, corporate governance and corporate social responsibility account for 47% of the performance of the firm. The results offer applicability and relevance of upper echelon, agency and stakeholder theories in normal organizational operations. While recruiting top managers, the selection board is guided to match the characteristic profiles of candidates against the members of the existing management team. In practice, firms attain superior performance if they incorporated good corporate governance with an independent board chairman, specialized board committees, and more outside directors on their boards. Organizations should mainstream corporate social responsibility practices that are consistent with expected societal expectations to stimulate higher performance. Policy makers are encouraged to be support manpower development, encourage improvement in governance and emphasize moral organizational value system as part of institutional conditions that impact on manufacturing performance in the local context as they formulate policies to aid competiveness of the sector projected in Kenya Vision 2030. The empirical testing in this paper adds to the scholarly knowledge by providing evidence on the synergistic effect of top management characteristics, corporate governance and social responsibility on firm performance. It goes further to contribute to literature on upper echelons theory, agency theory, stakeholder theory and organizational performance theory.